MiR-206 regulates the Th17/Treg ratio during osteoarthritis - Xiguang Ye; Qilin Lu; Aofei Yang; Jun Rao; Wei Xie; Chengjian He; Weijun Wang; Hao Li; Zhiwen Zhang (BMC, 2021)
Abstract Background The present study aimed to determine the functional role of miR-206 in T helper 17 (Th17)/regulatory T (Treg) cell differentiation during the development of osteoarthritis (OA). Methods Patients with OA and healthy controls were recruited for investigating the association between miR-206 and Th17/Treg ratio. Transfection experiments were conducted in CD4+ T cells to verify the mechanism of miR-206 on the balance of Treg/Th17. OA model was constructed to detect the clinical score, histopathological changes and Treg/Th17 ratio. OA model was induced in rats to verify the effect of miR-206 inhibition on Th17/Treg immunoregulation. Results High expression of miR-206 was positively correlated with peripheral Th17/Treg imbalance in patients with OA. The interactions between miR-206 and the 3' untranslated regions (3'-UTR) of suppressor of cytokine signaling-3 (SOCS3) and fork head transcriptional factor 3 (Foxp3) were confirmed by luciferase reporter assays. MiR-206 disturbed the Th17/Treg balance by targeting SOCS3 and Foxp3. In vivo assay demonstrated that antagomiR directed against miR-206 restored Th17/Treg balance during the development of OA. Conclusion MiR-206 contributed to the progression of OA by modulating Th17/Treg imbalance, suggesting that miR-206 inhibition might be a promising therapeutic strategy for the treatment of OA.